SUMBER DAYA ENERGI DAN MINERAL TERHADAP PEMBANGUNAN EKONOMI INDONES - Wawan Hermawan (Center for Economic Studies Universitas Katolik Parahyangan, 2004)
Energy consumption for driving economy in many countries has the crucial problem to maintain the sustainable development. The limited stock for energy that comes from fossil fuel resources has come to make the economic to be more efficient. More efficient in the phrase of sustainable social welfare intake. This paper talk with the condition of energy consumption in Indonesia and how the implication to economic development.